2009
DOI: 10.1152/physiolgenomics.90360.2008
|View full text |Cite
|
Sign up to set email alerts
|

Salty dog, an SLC5 symporter, modulatesDrosophilaresponse to salt stress

Abstract: To regulate their internal environments, organisms must adapt to varying ion levels in their diet. Adult Drosophila were exposed to dietary salt stress, and their physiological, survival, and gene expression responses monitored. Insects continued to feed on NaCl-elevated diet, although levels >4% wt/vol ultimately proved fatal. Affymetrix microarray analysis of flies fed on diet containing elevated NaCl showed a phased response: the earliest response was widespread upregulation of immune genes, followed by upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 45 publications
2
71
0
Order By: Relevance
“…Accordingly, we exposed the flies to salt stress. We and others have previously shown that a diet supplemented with 4% wt/vol NaCl is lethal to wild type (WT) Drosophila over several days (25). When WT flies were compared with either Nha1 or Nha2 knockdowns, or Nha1/Nha2 double knockdown escapers, it was obvious that NHA knockdowns reduced survival time on a NaCl diet (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Accordingly, we exposed the flies to salt stress. We and others have previously shown that a diet supplemented with 4% wt/vol NaCl is lethal to wild type (WT) Drosophila over several days (25). When WT flies were compared with either Nha1 or Nha2 knockdowns, or Nha1/Nha2 double knockdown escapers, it was obvious that NHA knockdowns reduced survival time on a NaCl diet (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Survival assays were performed as described previously (25). In brief, 7-d-old adult female flies were taken from their vials, kept in empty vials for 4 h to ensure prompt subsequent feeding, and then transferred in groups of 20-30 to vials containing a normal diet supplemented with different concentrations of NaCl or KCl.…”
Section: Methodsmentioning
confidence: 99%
“…Members of the immune induced molecule family are also highly induced. These transcripts have been found to be associated with the activation of Toll and JAK/STAT pathways of immunity (Kwon et al 2008) and with salt-stressed flies (Stergiopoulos et al 2009).…”
Section: Ex1mentioning
confidence: 99%
“…The fruit fly Drosophila is also capable of precise haemolymph osmoregulation in response to addition of 300mmoll -1 sucrose or NaCl to the diet (Pierce et al, 1999), or during dehydration and rehydration (Albers and Bradley, 2004). Most genes that are upregulated or downregulated by salt stress are highly enriched in the Malpighian tubules and/or the hindgut, suggesting that these tissues play major roles in the response to salt stress (Stergiopoulos et al, 2008). There is a robust increase in carbohydrate metabolism during salt stress, and expression of the GLUT4/8-like sugar transporter gene CG6484 is elevated 2700-fold in the midgut, relative to whole flies, whereas expression of the putative sodium/halide symporter gene salty dog (CG2196) is 7000-fold higher in the Malpighian tubules than in whole flies (Stergiopoulos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Most genes that are upregulated or downregulated by salt stress are highly enriched in the Malpighian tubules and/or the hindgut, suggesting that these tissues play major roles in the response to salt stress (Stergiopoulos et al, 2008). There is a robust increase in carbohydrate metabolism during salt stress, and expression of the GLUT4/8-like sugar transporter gene CG6484 is elevated 2700-fold in the midgut, relative to whole flies, whereas expression of the putative sodium/halide symporter gene salty dog (CG2196) is 7000-fold higher in the Malpighian tubules than in whole flies (Stergiopoulos et al, 2008). In addition, two proteins encoded by the inebriated (ine) gene have been implicated in osmolyte transport within the Malpighian tubule and hindgut.…”
Section: Introductionmentioning
confidence: 99%